Teachers’ self-efficacy in dealing with bullying among secondary schools students in Malaysia - Lee, J.C.; Narawi, M.S.; Abdul Rahman, N.A. (JESS, 2016)
It is no doubt that bullying has a lot of negative consequences on students and the most worrying part is that some victims of bullying even took away their own life or thinking about committing suicide. Evidences from a number of studies suggest that generally teachers are not very effective when they address or deal with cases of bullying in schools. Although there is now a considerable literature on the steps schools can take in dealing with cases of bullying, curiously enough there is little information available about what school teachers actually feel, think, and do when bullying is going on at their schools. Scant attention has been paid to school teachers’ self-efficacy regarding dealing with bullying particularly in Malaysia. The purpose of this study was to identify the levels of secondary schools teachers’ self-efficacy (behavioral, Cognitive, and Emotional) in terms of dealing with bullying among students. Responses to sense of efficacy when dealing with bullying among students in secondary schools were sought from 1920 in-service teachers from 120 secondary schools which had been randomly selected from 6 out of 13 states in Malaysia. Based on the finding of this study, Behavioral Self- Efficacy has the highest overall mean followed by Cognitive Self-efficacy and Emotional Self-efficacy. However, the level of agreement towards teacher’s Behavioral Efficacy in dealing with bullying, from both students and parents involved in this study is considered quite low. With better training opportunities and ongoing professional development for teachers to enhanced their behavioral, cognitive, and emotional efficacy in dealing with bullying hopefully will help to ease the problem of bullying in schools.